The Stress Burden and Positive Coping Among the United Arab Emirates Population During Crisis: A Cross-sectional Study from the Pandemic Era - Yousef M. Aljawarneh; Lubna M. Rajab; Maha S. Alyileili; Roqayah S. Alkaabi; Shaikha H. Alhooti; Thekra A. Alnuaimi; Hana Y. Ghunaim (Dubai Medical Journal)
Introduction: The pandemic crisis created a psychosocial and public health crisis that affected the lives of millions globally. This cross-sectional study aims to examine the stress burden during the pandemic crisis and positive coping among the general population in the United Arab Emirates (UAE). Methods: This study employed a crosssectional design to examine the stress burden of the pandemic crisis and positive coping among the general population in the UAE. The study questionnaires were sent to potential participants as an online survey. A total of 465 UAE residents were enrolled between October and December 2021. The stress burden and positive coping were measured using the Coronavirus Disease of 2019 Pandemic Mental Health Questionnaire (CoPaQ).